Aspectos de la biología y patogenicidad del hongo Metarhizium anisoplae (Metchnikoff) Sorokin, sobre Aeneolamia varia (F). (1988)
The fungus Metarhizium unisopliae (Metch.) Sorokin was isolated from the insect Aeneolamia varia (F) collected from Brachiaria clecumbens signalgrass in ICA, Experimental Station "La Libertad" at Villavicencio. Laboratory studies showed that nymphs less than 15 days old of A. varia are the stage most susceptible to the parasitism of M.anisopliae. Pathogen infectivity decreased as fungus dosage decreased; a concentration of 3.6 x 10 spores/mI 62.75% mortality in nymphs was observed, and only 4.72% of dead nymphs when concentration was 3.6 x iOn. In biological studies of the fungus it was determined that the media with potato dextrose agar (PDA) and Sabouraud dextrose agar at 21 .1°C and 20.6°C respectively, were satisfactory for the normal growth. Highest sporulation was observed on PDA; however, M. anisopliae showed a good sporulation in boiled rice medium at a temperature of 25°C ± 1°C. The sporulation peak was observed 18.9 days after inoculation in this medium, and spore germination was 59.8% average at 26°C, and 100% relative humidity.